THE APPLICATION OF INFORMATION TECHNOLOGY IN IMPROVING INNOVATION PERFORMANCE FOR STUDENT ENTREPRENEURS - Indah Wahyu Utami; Eko Purwanto; Diana Novira; Fioga Zahra Fernando (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
A business organization is always with products, business processes, and innovations. As a process of managing business innovation management so that it can create a sustainable competitive advantage. Efforts to create an effect on innovation performance require synergy in innovation performance and information technology. So that the business can be sustainable and support the competitiveness of student entrepreneurs. The purpose of this study is to determine the application of information technology to improve innovation performance management for student entrepreneurs. The sample in this study was 100 student entrepreneurs at some private universities in Surakarta. This study used a quantitative descriptive research design. Research by distributing questionnaires to respondents obtained results that student entrepreneurs Most of them have utilized information technology in business management. The business fields carried out by the respondents in this study include culinary, service, beauty, and fashion.